Complement clauses in Portuguese syntax and acquisition - Santos, Ana Lúcia; Gonçalves, Anabela (Issues in Hispanic and Lusophone linguistics (IHLL),, 2018)
"This volume addresses core issues on complement clauses, focusing on Portuguese (European, Brazilian and Mozambican varieties). It contributes to the discussion of complementation, providing an overview of how theoretical syntax and acquisition studies may combine to broaden our knowledge about the topic. The articles are organized in two sections, each one followed by a comment paper: the first section, more theoretical in its nature, gathers contributions analyzing major syntactic aspects of complementation in Portuguese, from a synchronic and a diachronic point of view; the second section includes articles on L1 and L2 acquisition of Portuguese complementation. Both sections especially focus on infinitival structures; mood selection and the interpretation of subjects in finite complement clauses are also topics of particular relevance. The volume is meant for researchers and students interested in formal syntax and acquisition in general and Portuguese syntax and acquisition in particular"--